The Heterogeneity of Disruptive Behavior Disorders – Implications for Neurobiological Research and Treatment - Stadler, Christina; Poustka, Fritz; Sterzer, Philipp (Frontiers in Psychiatry, 2010)
Disruptive behaviour disorders are reflected by a great variety of symptoms ranging from impulsive-hot tempered quarrels to purposeful and goal directed acts of cruelty. A growing body of data indicates that there are neurobiological factors that increase the risk for developing disruptive behaviour disorders. In this review, we give a broad overview of recent studies investigating physiological, neural, genetic factors, and specific neurotransmitter systems. We also discuss the impact of psychosocial risk and consider the effects of gene-environment interactions. Due to the heterogeneity of disruptive behaviour disorders, it is concluded that specific subtypes of disruptive behaviour should be considered both in terms their biological basis and in regard to specific treatment needs.